Students’ Motivation and Appreciation on The Teaching of Writing Short Story Based on Creative-Literacy - Sitti Rachmi Masie; Wahyudi Siswanto; Yuni Pratiwi; Heri Suwignyo (Journal of Educational Science and Technology (EST), 2017)
This paper is initiated by the writers’ preliminary observation regarding  literary work learning activities in  the Department of Indonesian  Education and Literature State University of Gorontalo, which is still experiencing problems in its   learning process. One of the obstacles faced is that students are still lack of confidence in developing their ability to write literary works, especially writing short stories. Writing short stories based on creative literacy is a strategy given to develop the competence of learners in writing. Short story is chosen because it has an interesting characteristics so students will easily read and understand it. Using this strategy, it is expected that students are able to write short stories based on the results of their own creation. Writing short stories based on creative literacy can  manifest students’  ability in identifying various text forms, the purpose of the text, the text readers’ target, and it enables the students to use their thinking ability to organize their process of reading and writing their new work.